Assessing Socio-Economic Sustainability in Coastal Tourism Destinations of North Jakarta, Indonesia - Dewi Gita Kartika; Ina Gandawati Djamhur; Ismayanti (Journal of Enterprise and Development (JED), 2024)
Purpose: This research aims to evaluate the socio-economic sustainability of 12 coastal tourism destinations in North Jakarta, recognized since 2011, by assessing their levels of social and economic sustainability.Method: The study uses a descriptive research design with a quantitative approach, employing scoring analysis techniques. Data were collected through observations and Focus Group Discussions (FGDs) with key informants from the 12 coastal tourism destinations in North Jakarta.Result: The scoring-based evaluation ranked the 12 destinations based on their socio-economic sustainability performance. Four areas—Kelapa Gading, Sunda Kelapa, Tanjung Priok, and Ancol—were categorized as highly sustainable, while Bahtera Jaya Yacht Club was identified as the least socio-economically sustainable. Overall, the 12 coastal tourism destinations in North Jakarta were classified as fairly sustainable from a socio-economic perspective.Practical Implications for Economic Growth and Development: This study identifies key areas for enhancing socio-economic sustainability in 12 coastal tourism destinations, which can inform policy and investment decisions to boost local economies and stimulate growth in surrounding sectors such as creative industries, trade, and services, by promoting local products and increasing income for local businesses.